An introduction to radical participatory design: decolonising participatory design processes. (20th December 2022) - Udoewa, Victor
Abstract: Outside of community-led design projects, most participatory design processes initiated by a company or organisation maintain or even strengthen power imbalances between the design organisation and the community on whose purported behalf they are designing, further increasing the absencing experience. Radical participatory design (RPD) is a radically relational answer to the coloniality inherent in participatory design where the community members' disappointment is greater due to the greater expectations and presencing potential of a 'participatory design' process. We introduce the term RPD to show how research and design processes can be truly participatory to the root or core. Instead of treating participatory design as a method, a way of conducting a method, or a methodology, we introduce RPD as a meta-methodology, a way of doing any methodology. We explicitly describe what participation means and compare and contrast design processes based on the amount of participation, creating a typology of participation. We introduce 'designer as community member', 'community member as designer, ' and 'community member as facilitator' models and provide characteristics for the meta-methodology of RPD.